Oral Health Literacy, Preventive Behavior Measures, and Chronic Medical Conditions. (July 2018) - Messadi, D.V.; Macek, M.D.; Markovic, D.; Atchison, K.A.
The purpose of this study was to examine the association between oral health literacy, preventive orientation and behaviors, and chronic medical conditions—specifically, hypertension and diabetes. A cross-sectional study was conducted with dental school patients attending the dental clinics in Los Angeles, California, and Baltimore, Maryland. Their health literacy levels were measured using the short Test of Functional Health Literacy in Adults (Short-TOFHLA) and the Rapid Estimate of Adult Literacy in Medicine and Dentistry (REALM-D). The medical history and existing medical conditions—specifically, hypertension and diabetes status—were extracted from patient health history and electronic records. Ten items were asked about preventive behaviors (e.g., brushing teeth in evening, smoking, exercise, drinking soda) and 3 preventive health services (dental checkup, flu shot, medical checkup). Six locus of control items were asked (e.g., good health is a matter of good fortune, what happens to my health is God's will). Out of 793 subjects, 221 had a documented history of hypertension, 88 with diabetes. There was an association between Short-TOFHLA scores and both diabetes and hypertension, but after controlling for sociodemographic and preventive variables, the association was no longer significant. In multivariate analysis, women, people with at least some college, Asians or non-Hispanic Whites, younger people, those who spoke English as a child, those who sought health information from the Internet or health care professionals, and those who smoked reported lower utilization of preventive health services, and those who had less locus of control reported higher Short-TOFHLA scores. There were no significant differences in mean REALM-D scores between patients who had hypertension or diabetes versus not having the condition. Multivariate models showed that people with higher REALM-D scores had at least some college, were other race/ethnicity or non-Hispanic White, spoke English as a child, and sought health information via the Internet. Knowledge Transfer Statement: The results of this study show that dental school patients exhibit a range of health literacy abilities and preventive behaviors, and health literacy measures positively correlated with some preventive behaviors but not others. Dental schools receive a significant number of patients with chronic diseases, and students should be educated to use effective patient communication skills to reinforce positive health behaviors among these patients.